2023
DOI: 10.1111/1755-0998.13907
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and taxonomic diversity of mesozooplankton is an important driver of carbon export fluxes in the ocean

Margaux Perhirin,
Hannah Gossner,
Jessica Godfrey
et al.

Abstract: Mesozooplankton is a very diverse group of small animals ranging in size from 0.2 to 20 mm not able to swim against ocean currents. It is a key component of pelagic ecosystems through its roles in the trophic networks and the biological carbon pump. Traditionally studied through microscopes, recent methods have been however developed to rapidly acquire large amounts of data (morphological, molecular) at the individual scale, making it possible to study mesozooplankton using a trait‐based approach. Here, combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 140 publications
1
0
0
Order By: Relevance
“…However, we did not find a statistically significant correlation between export efficiency and the NBSS slope (although the non-significant correlation was positive, as predicted, Figure 6b). Our results also align with a recent study from the Sargasso Sea showing that zooplankton size did not correlate with export flux (Perhirin et al, 2024). That study also showed that opacity was an important zooplankton trait that correlated strongly with export flux, and although we could not quantify opacity from our dataset, several of our highest export efficiency locations (from the SalpPOOP cruise, Décima et al, 2023) were measured within a bloom of highly transparent pelagic tunicates.…”
Section: Discussionsupporting
confidence: 91%
“…However, we did not find a statistically significant correlation between export efficiency and the NBSS slope (although the non-significant correlation was positive, as predicted, Figure 6b). Our results also align with a recent study from the Sargasso Sea showing that zooplankton size did not correlate with export flux (Perhirin et al, 2024). That study also showed that opacity was an important zooplankton trait that correlated strongly with export flux, and although we could not quantify opacity from our dataset, several of our highest export efficiency locations (from the SalpPOOP cruise, Décima et al, 2023) were measured within a bloom of highly transparent pelagic tunicates.…”
Section: Discussionsupporting
confidence: 91%